From Immanence to Becoming: Beauvoir, Nietzsche, and the Feminist Monologue in The Patience Stone - Abas, Chaker (European Scientific Journal, ESJ, 2025)
The article explores the feminist existentialist dimensions of Atiq Rahimi’s The Patience Stone (2008), situating the unnamed female protagonist’s radical monologue within a broader philosophical lineage that includes Simone de Beauvoir and Friedrich Nietzsche. Drawing on Beauvoir’s The Ethics of Ambiguity (2004) and Nietzsche’s The Gay Science (1974) the stusy frames the woman’s struggle against immanence and patriarchal silencing as a philosophical revolt. Beauvoir’s humanist existentialism provides a lens for understanding the protagonist’s resistance to passive identity, while Nietzsche’s concept of revaluation of values illuminates her defiant articulation of desire, trauma, and agency. The protagonist’s transformation from passive to self-authoring entity echoes Nietzschean call to transcenf herd morality and affirm the self through creative resistance. By bridging Beauvoir’s ethics with Nietzsche’s radical critique of moral normativity, this study argues that The Patience Stone stages a feminist revolt that is both existential and genealogical - dismantling inherited structures of meaning while forging new modes of becoming. Ultimately, enacts a philosophical drama of voice, vulnerability, and value creation in a context where silence has long been mistaken for virtue.